Advances in Pillared Clays and Similar Materials Synthesis, Characterization and Applications - Gil Bravo, Antonio; Vicente, Miguel A. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Since the first works introducing the aluminum intercalated clay family in the early 1970s, interest in the synthesis of Pillared InterLayered Clays (PILC) has increased tremendously, especially research into their properties and energetic and environmental applications. After our comprehensive reviews and book on the synthesis and catalytic applications of these materials, new references have appeared in the literature and the interest in this field is continuously increasing. The aim of this Special Issue is to collect the recent advances developed considering this family of solids.